CHILD SEXUAL ABUSE, BULLYING, CYBERBULLYING, AND MENTAL HEALTH PROBLEMS AMONG HIGH SCHOOLS STUDENTS: A MODERATED MEDIATED MODEL - Hébert, Martine (Depress Anxiety, 2016)
Child sexual abuse is associated with adverse outcomes, including heightened vulnerability that may translate into risk of revictimization. The aims of the study were: (1) to explore the direct and indirect links between child sexual abuse and cyberbullying, bullying, and mental health problems and (2) to study maternal support as a potential protective factor. Methods: Teenagers involved in the two first waves of the Quebec Youths’ Romantic Relationships Survey (N = 8,194 and 6,780 at Wave I and II, respectively) completed measures assessing child sexual abuse and maternal support at Wave I. Cyberbullying, bullying, and mental health problems (self-esteem, psychological distress, and suicidal ideations) were evaluated 6 months later. Results: Rates of cyberbullying in the past 6 months were twice as high in sexually abused teens compared to nonvictims both for girls (33.47 vs. 17.75%) and boys (29.62 vs. 13.29%). A moderated mediated model revealed a partial mediation effect of cyberbullying and bullying in the link between child sexual abuse and mental health. Maternal support acted as a protective factor as the conditional indirect effects of child sexual abuse on mental health via cyberbullying and bullying were reduced in cases of high maternal support. Conclusions: Results have significant relevance for prevention and intervention in highlighting the heightened vulnerability of victims of child sexual abuse to experience both bullying and cyberbullying. Maternal support may buffer the risk of developing mental health distress, suggesting that intervention programs for victimized youth may profit by fostering parent involvement.